Determination of factors influencing the quality of a hot coffee drink - Kuzmin, Oleg; Popyk, Oleg; Stukalska (Ivanova), Nataliia; Polovyk, Volodymyr (My University, 2022)
The specified influence factors have methodological importance of the problem that is under consideration and requires multifaceted research in the practice of restaurant service technologies in the aspect of making hot coffee drinks.
Keywords: кафедра технології ресторанної і аюрведичної продукції; modern market; hot drink; coffee